The Challenge of the Pathogenesis of Parkinson's Disease: Is Autoimmunity the Culprit? - Jiang, Tianfang; Li, Gen; Xu, Jun; Gao, Shane; Chen, Xu (Frontiers in Immunology, 2018)
The role of autoimmunity in Parkinson’s disease (PD), as one of the most popular research subjects, has been intensively investigated in recent years. Although the ultimate cause of PD is unknown, one major area of interest remains identifying new therapeutic targets and options for patients suffering from PD. Herein, we present a comprehensive review of the impacts of autoimmunity in neurodegenerative diseases, especially PD, and we have composed a logical argument to substantiate that autoimmunity is actively involved in the pathogenesis of PD through several proteins, including α-synuclein, DJ-1, PINK1 and Parkin, as well as immune cells, such as dendritic cells, microglia, T cells and B cells. Furthermore, a detailed analysis of the relevance of autoimmunity to the clinical symptoms of PD provides strong evidence for the close correlation of autoimmunity with PD. In addition, the previously identified relationships between other autoimmune diseases and PD help us to better understand the disease pattern, laying the foundation for new therapeutic solutions to PD. In summary, this review aims to integrate and present currently available data to clarify the pathogenesis of PD and discuss some controversial but innovative research perspectives on the involvement of autoimmunity in PD, as well as possible novel diagnostic methods and treatments based on autoimmunity targets.